Stability of P_2 Methods for Neutron Transport Equation (Journal of Partial Differential Equations, 2002)
" In this paper the P_2 approximation to the one-group planar neutron transport theory is discussed. The stability of the solutions for P_2 equations with general boundary conditions, including the Marshak boundary condition, is proved. Moreover, the stability of the up-wind difference scheme for the P_2 equation is demonstrated."
Keywords: Neutron transport equations; Up-wind schemes; Stability